Fibrinogen-to-prealbumin ratio: A new prognostic marker of resectable pancreatic cancer - Li, Chengqing; Fan, Zhiyao; Guo, Wenyi; Liang, Feng; Mao, Xincheng; Wu, Jiahao; Wang, Haodong; Xu, Jianwei; Wu, Dong; Liu, Han; Wang, Lei; Li, Feng (Frontiers in Oncology, 2023)
Background: The fibrinogen-to-prealbumin ratio (FPR), a novel immune-nutritional biomarker, has been reported to be associated with prognosis in several types of cancer, but the role of FPR in the prognosis of resectable pancreatic cancer has not been elucidated. Methods: A total of 263 patients with resectable pancreatic cancer were enrolled in this study and were randomly divided into a training cohort (n = 146) and a validation cohort (n = 117). Receiver operating characteristic curve (ROC) was used to calculate the cut-off values of immune-nutritional markers. The least absolute shrinkage and selection operator (LASSO) regression and multivariate Cox regression were performed in the training cohort to identify the independent risk factors, based on which the nomogram was established. The performance of the nomogram was evaluated and validation by the training and validation cohort, respectively. Results: The optimal cutoff value for FPR was 0.29. Multivariate analysis revealed that FPR, controlling nutritional status (CONUT), carbohydrate antigen 19-9 (CA19-9), carcinoembryonic antigen (CEA), and tumor node metastasis (TNM) stage were independent predictors of overall survival (OS). The nomogram was established by involving the five factors above. The C-index of the training cohort and validation cohort were 0.703 (95% CI: 0.0.646-0.761) and 0.728 (95% CI: 0.671-0.784). Decision curve analysis and time-dependent AUC showed that the nomogram had better predictive and discriminative ability than the conventional TNM stage. Conclusion: FPR is a feasible biomarker for predicting prognosis in patients with resectable pancreatic cancer. The nomogram based on FPR is a useful tool for clinicians in making individualized treatment strategies and survival predictions.